2018
DOI: 10.1016/j.epsl.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

A simple biomineralization model to explain Li, Mg, and Sr incorporation into aragonitic foraminifera and corals

Abstract: In contrast to Li/Ca and Mg/Ca, Li/Mg is strongly anticorrelated with growth temperature in aragonites precipitated by the benthic foraminifer Hoeglundina elegans and a wide range of scleractinian coral taxa. We propose a simple conceptual model of biomineralization that explains this pattern and that is consistent with available abiotic aragonite partition coefficients. Under this model the organism actively modifies seawater within its calcification pool by raising its [Ca 2+ ], using a pump that strongly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 75 publications
7
76
0
Order By: Relevance
“…For instance, it has been suggested that Mg 2+ and Li + are both transported to the site of calcification via the direct paracellular transport of ambient seawater before being incorporated into the aragonite crystal by similar physicochemical mechanisms that still remain the subject of active debate (Case et al, 2010;Paolo Montagna et al, 2014;Rollion-Bard & Blamart, 2015). Regardless of the specific mechanisms, differences in biogenic crystal growth mechanics appear to have little direct effect on the Li/Mg ratio in the coral skeleton, thus making this a relatively robust proxy for ambient seawater temperature that is essentially independent of vital effects (Marchitto et al, 2018;Paolo Montagna et al, 2014;P. Regardless of the specific mechanisms, differences in biogenic crystal growth mechanics appear to have little direct effect on the Li/Mg ratio in the coral skeleton, thus making this a relatively robust proxy for ambient seawater temperature that is essentially independent of vital effects (Marchitto et al, 2018;Paolo Montagna et al, 2014;P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been suggested that Mg 2+ and Li + are both transported to the site of calcification via the direct paracellular transport of ambient seawater before being incorporated into the aragonite crystal by similar physicochemical mechanisms that still remain the subject of active debate (Case et al, 2010;Paolo Montagna et al, 2014;Rollion-Bard & Blamart, 2015). Regardless of the specific mechanisms, differences in biogenic crystal growth mechanics appear to have little direct effect on the Li/Mg ratio in the coral skeleton, thus making this a relatively robust proxy for ambient seawater temperature that is essentially independent of vital effects (Marchitto et al, 2018;Paolo Montagna et al, 2014;P. Regardless of the specific mechanisms, differences in biogenic crystal growth mechanics appear to have little direct effect on the Li/Mg ratio in the coral skeleton, thus making this a relatively robust proxy for ambient seawater temperature that is essentially independent of vital effects (Marchitto et al, 2018;Paolo Montagna et al, 2014;P.…”
Section: Introductionmentioning
confidence: 99%
“…While inorganic experiments suggest that Li + is incorporated into aragonite through heterovalent substitution for Ca 2+ (as opposed to homovalent substitution by Mg 2+ ; Marriott et al, 2004), other experimental and theoretical evidence suggests that both Li and Mg are incorporated through defects of the aragonite crystal (Paolo Montagna et al, 2014) and/or some other entrapment processes (Finch & Allison, 2008;Watson, 1996Watson, , 2004. Regardless of the specific mechanisms, differences in biogenic crystal growth mechanics appear to have little direct effect on the Li/Mg ratio in the coral skeleton, thus making this a relatively robust proxy for ambient seawater temperature that is essentially independent of vital effects (Marchitto et al, 2018;Paolo Montagna et al,…”
Section: Introductionmentioning
confidence: 99%
“…These issues have prompted the development of alternative paleothermometers, such as Li/Ca (Marriott et al, ) and Li/Mg (Case et al, ; Hathorne, Felis, et al, ; Lear et al, ; Montagna et al, ; see also Fowell et al, ; Marchitto et al, ). Since both Li + and Mg 2+ are not preferentially incorporated into the aragonite lattice ( K D << 1), the ratio of [Li + ]/[Mg 2+ ] remains relatively constant in the calcifying fluid as precipitation proceeds, even though [Ca 2+ ] would be expected to decline (Montagna et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since both Li + and Mg 2+ are not preferentially incorporated into the aragonite lattice ( K D << 1), the ratio of [Li + ]/[Mg 2+ ] remains relatively constant in the calcifying fluid as precipitation proceeds, even though [Ca 2+ ] would be expected to decline (Montagna et al, ). Li/Mg is thought to be largely independent of Rayleigh fractionation and instead should reflect primarily the different temperature sensitivities of Li and Mg to incorporation (Hathorne, Felis, et al, ; Marchitto et al, ; Montagna et al, ). While a general exponential trend exists between Li/Mg and temperature (Marchitto et al, ; Montagna et al, ), some effects of species and location have been reported (Fowell et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation